ANALYSIS OF THE DEVELOPMENT OF ENTERPRISES PROVIDING HEALTH SERVICES IN UZBEKISTAN (Marketing Journal, 2025)
This article examines the current state and development trends of enterprises providing wellness services in Uzbekistan. It analyzes the dynamics of the hotel and sanatorium stock, describes the specifics of the infrastructure and the range of wellness services offered. Key issues and prospects for the development of wellness tourism in the republic are identified, taking into account global trends and national characteristics. Measures are proposed to improve the quality and competitiveness of wellness ser vices in Uzbekistan.
Keywords: wellness services; tourism; hotels; sanatoriums; Uzbekistan; infrastructure